Biogenic carbon encapsulated iron oxides mediated oxalic acid for Cr(VI) reduction in aqueous: Efficient performance, electron transfer and radical mechanisms. (February 2023) - Gu, Chunyao; Cai, Miao; He, Peng; Zhu, Jianyu; Gan, Min
Abstract: Carbonaceous materials have a potential to mediated oxalic acid (OA) for Cr(VI) reduction, but the rational modification is needed for boosting the mediation of electron transfer. Herein, we utilized polyvinyl alcohol to envelop schwertmannite synthesized by Acidithiobacillus ferrooxidans biomineralization, and pyrolyzed them to obtain the carbon encapsulated iron oxides (C-2.0- Sch -PVA). SEM and TEM results demonstrated that a moderate calcination temperature would yield a neural network-like carbon encapsulated structure. C-2.0- Sch -PVA efficiently mediated OA to reduce Cr(VI), 98.4% of Cr(VI) (40 mg L −1 ) was reduced with 0.75 g L −1 C-2.0- Sch -PVA and 4 mM OA in 60 min. It still performed excellent results in a wide pH range, multiple anions and different water matrixes. The carbon encapsulated structure as electron shuttle mediated the electron transfer, and the O-moieties on its surface were a premise for initiating the Cr(VI) reduction process. The electron transfer from the inner iron oxides to the conjugated structure of the outer carbon shells facilitated Cr(VI) reduction as well. Moreover, OA raised the persistent free radicals' level in C-2.0- Sch -PVA as another important pathway for Cr(VI) reduction. Overall, C-2.0- Sch -PVA provides an excellent demonstration in the carbonaceous materials modification for mediating OA to reduce Cr(VI) in aqueous. Graphical abstract: Image 1 Highlights: Carbon encapsulated iron oxides was synthesized by biomineralization and pyrolysis. Carbon encapsulated structure as electron shuttle mediated OA to reduce Cr(VI). The inner iron oxide as another electron source enhanced the electron transfer. The O-moieties were a premise for initiating the Cr(VI) reduction process. Oxalic acid raised the PFRs level in C-2.0- Sch -PVA and facilitated Cr(VI) reduction.